Anonymous [videorecording (DVD)] - Emmerich, Roland; Ifans, Rhys, 1967-; Redgrave, Vanessa, 1937-; Thewlis, David, 1963- (Columbia Pictures Industries, 2012)
Was Shakespeare a fraud? Who really wrote about cloak-and-dagger political intrigue, illicit romances in the Royal Court, and the schemes of greedy nobles hungry for the power of the throne? Set against the backdrop of the succession of Queen Elizabeth I, and the Essex Rebellion against her, intrigue and suspense advance the theory that it was really Edward De Vere, Earl of Oxford, who penned Shakespeare's plays.